Locoregional Therapies and Interventional Radiology in Managing Hepatocellular Carcinoma: A Comprehensive Approach to Bridging, Downstaging, and Liver Transplantation - Barrera, Juana V.; Dallag, Leonard; Akram, Rubeel; Salsamendi, Jason; Barragan, Camilo; Wehrle, Chase J.; Benjamin, Jamaal; Molano, Maria del Pilar Bayona (Digestive Disease Interventions, 2024)
Hepatocellular carcinoma (HCC) remains a significant global health challenge, particularly for patients awaiting liver transplants (LTs) due to the scarcity of donor organs. During the waiting period, a multidisciplinary approach becomes crucial to optimize tumor treatment and preserve liver function. In recent years, interventional radiology has emerged as an integral part of treatment strategies. It has played a pivotal role in bridging and downstaging patients on the path to transplantation. Interventional radiologists administer minimally invasive locoregional therapies to HCC patients on LT waiting lists. Additionally, they address complications such as portal hypertension and portal vein thrombosis, which can lead to clinical deterioration and jeopardize transplant candidacy. This article examines the pivotal role of interventional radiology in the management of HCC, highlighting recent studies and advancements within the field. Additionally, it provides a concise review of the eligibility criteria for LT in patients with HCC, alongside a discussion of the surgical techniques employed in LT for these patients.
Keywords: hepatocellular carcinoma; interventional radiology; locoregional therapy